Hash-Polar Codes With Application to 5G - Peiyao Chen; Baoming Bai; Zhaofeng Ren; Jiaqing Wang; Shaohui Sun (IEEE Access, 2019)
This paper presents a kind of concatenated polar codes called hash-polar codes with flexible outer code lengths, in which a hash function-based encoder is used as an outer encoder. A partial hash-polar code is also proposed to enhance the error-correcting performance at high signal-to-noise ratios. Since polar codes have been recommended by 3GPP as the channel coding scheme for the 5G enhanced mobile broadband control channel, the design of hash-polar codes for 5G is considered, where both good error-correcting performance and low false alarm rate (FAR) are required. The simulation results show that, under the 5G FAR requirement, the proposed hash-polar codes have similar frame error rate performance to cyclic redundancy check (CRC)-polar codes and perform better than parity check polar codes. In order to support early termination (ET) for 5G coding, we then propose segmented hash-polar codes, which exhibit the advantages of the ET gain compared with both CRC-polar codes and distributed CRC-polar codes.